Monoclonal Antibody-Mediated Modulation of the Humoral Immune Response against Mucosally Applied Streptococcus mutans - Brady, L. Jeannine (American Society for Microbiology, 2000)
Systemic immunization with antigen coupled to monoclonal antibody (MAb) has been used by several investigators to increase the number of MAb-producing hybridomas against an antigen and to elicit antibodies specific for poorly immunogenic epitopes. This strategy has implications for vaccine design in that protective immunity is not necessarily directed at immunodominant epitopes of pathogens and may be improved by deliberately shifting the immune response toward subdominant epitopes. To our knowledge, no studies to date have addressed the potential for immunomodulatory activity mediated by MAbs bound to mucosally applied antigen. To test whether administration of an exogenous MAb directed against a streptococcal surface protein could influence the humoral immune response, BALB/c mice were immunized orally by gastric intubation or intranasally with Streptococcus mutans alone or S. mutans complexed with a MAb directed against the major surface protein P1. Significant changes in the subclass distribution, as well as the specificity, of anti-P1 serum immunoglobulin G antibodies were demonstrated in groups of mice which received S. mutans coated with the anti-P1 MAb versus those which received S. mutans alone. Alterations in the humoral immune response were dependent on the amount of anti-P1 MAb used to coat the bacteria. In addition, differences in the anti-P1 immune responses were observed between groups of mice immunized via oral versus intranasal routes. In summary, an exogenous MAb complexed with a streptococcal antigen prior to mucosal immunization can influence the immunoglobulin isotype and specificity of the host humoral immune response against the antigen.